Вплив стимулюючої підгодівлі на розвиток бджолиних сімей - Кучер, С. О.; Kucher, S. O.; Милостивий, Роман Васильович; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Mylostyvyi, Roman V.; Mylostyvy, R.; Mylostyvyi, R.; Milostivyi, R. (ДУ Інститут зернових культур НААН, 2024)
Метою роботи було дослідити ріст і розвиток бджолиних сімей користувальної групи за використання стимулюючої підгодівлі. Дослідження проведені навесні 2023 року в умовах пасіки сільськогосподарського обслуговуючого кооперативу «Дніпровський пасічник» Солонянського району Дніпропетровської області. To maintain and increase the number of productive bee colonies and prevent swarming, laying is performed. The formation of packages and laying involves the involvement of strong Apis mellifera sossimae bee families, which must have a sufficient number of brood and young worker bees, which cannot be achieved without stimulating feeding. A greater positive effect on the reproductive function of queen bees and the growth of bee families was found when adding Kandy feeding paste compared to feeding with sugar syrup. The use of the paste increases the strength of families by 2.08 times.
Effect of stimulating feeding on the development of bee families
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: підгодівля бджіл; pidhodivlia bdzhil; бджолині сім’ї; bdzholyni simi; бджільництво; bdzhilnytstvo